PENILAIAN OTENTIK - Burhan Nurgiyantoro (LPMPP Universitas Negeri Yogyakarta, 2008)
AbstractIn the era of Competency-Based Curriculum/School-Based Curriculum, theassessment emphasizes students performance in each subject. They are required toacquire not only the cognitive aspect but also the performance aspect. Oneassessment model relevant to this is the authentic assessment. Such an assessmentemphasizes students ability to meaningfully demonstrate the knowledge theyhave acquired. The assessment not only asks questions about the knowledge theyhave acquired, but also requires the actual performance relevant to the knowledge.There are some differences between a traditional assessment and an authenticassessment. The former emphasizes the elicitation of knowledge the students haveacquired through objective tests, while the latter emphasizes the tasks that makethe students practice meaningfully learning outcomes in real life, reflecting themastery of knowledge and skills in a particular subject. The necessary steps todevelop an authentic assessment include (1) setting the standard; (2) assigningauthentic tasks; (3) selecting the criteria; and (4) designing the rubric. One popularauthentic assessment at present is the portfolio assessment model. This model is aclass-based assessment conducted during the learning process. A portfolio is acollection of students works systematically arranged during a certain learningperiod, used to monitor the development of the students knowledge, skills, andattitudes in a particular subject.Keywords: authentic assessment, traditional assessment, portfolio